Natural Products Chemistry: Emerging Trends and Projected Goals - Agarwal, Shubhangee; Bhatt, Neha (Natural Products Chemistry: From Discovery to Applications, Edition 1, 2024)
The chemistry of natural products is anticipated to offer significant opportunities for the growth of the pharmaceutical, green chemical, and novel therapeutic industries in the future. Researchers are increasingly employing contemporary technologies such as genomics, metabolomics, and synthetic biology in traditional bio-prospecting and natural product discovery. This approach enhances the potential for identifying more complex bioactive compounds and elucidating their biosynthetic pathways. Furthermore, it is essential to prioritize a sustainable and conservation-oriented approach in the utilization of natural materials, ensuring that raw materials are sustainable for extended durability. The new initiative aimed at systematic research in natural product chemistry is projected to serve as a significant foundation for global health and sustainable environmental utilization.